Demonstrating an additional law of relativistic velocities based on squeezed light - 杨大宝 李艳 张福林 陈景灵 (Chinese physics B, 2012)
The special relativity is the foundation for many branches of modern physics, of which the theoretical results are far beyond our daily experience and hard to realized in kinematic experiments. However, its outcomes could be demonstrated by making use of the convenient substitute, i.e., the squeezed light in the present paper. The squeezed light is very important in the field of quantum optics, and the corresponding transformation can be regarded as the coherent state of SU（1,1）. In this paper, the connection between the squeezed operator and the Lorentz boost is built under certain conditions. Furthermore, the additional law of relativistic velocities and the angle of the Wigner rotation are deduced as well.